The relationship between visitors motivations and satisfactions at Kuala Lumpur Standard Chartered Marathon 2024 / Muhammad Faris Amirul Useri and Azman Ahmad Tajri - Useri, Muhammad Faris Amirul; Ahmad Tajri, Azman (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study investigates the relationship between visitor motivation and satisfaction at the Kuala Lumpur Standard Chartered Marathon 2024. It identifies key motivational and satisfaction factors and examines their significant interconnections. By understanding these dynamics, the research aims to enhance the overall visitor experience at the event. A non-experimental, quantitative approach using questionnaires was employed to collect data from 382 visitors of the Kuala Lumpur Standard Chartered Marathon 2024. Participants represented a diverse population of over 75,000 attendees. Pearson correlation analysis was conducted using Jamovi software to examine the relationship between visitor motivation and satisfaction.